CER4 Encodes an Alcohol-Forming Fatty Acyl-Coenzyme A Reductase Involved in Cuticular Wax Production in Arabidopsis - Rowland, Owen (American Society of Plant Biologists, 2006)
A waxy cuticle that serves as a protective barrier against uncontrolled water loss and environmental damage coats the aerial surfaces of land plants. It is composed of a cutin polymer matrix and waxes. Cuticular waxes are complex mixtures of very-long-chain fatty acids and their derivatives. We report here the molecular cloning and characterization of CER4, a wax biosynthetic gene from Arabidopsis (Arabidopsis thaliana). Arabidopsis cer4 mutants exhibit major decreases in stem primary alcohols and wax esters, and slightly elevated levels of aldehydes, alkanes, secondary alcohols, and ketones. This phenotype suggested that CER4 encoded an alcohol-forming fatty acyl-coenzyme A reductase (FAR). We identified eight FAR-like genes in Arabidopsis that are highly related to an alcohol-forming FAR expressed in seeds of jojoba (Simmondsia chinensis). Molecular characterization of CER4 alleles and genomic complementation revealed that one of these eight genes, At4g33790, encoded the FAR required for cuticular wax production. Expression of CER4 cDNA in yeast (Saccharomyces cerevisiae) resulted in the accumulation of C24:0 and C26:0 primary alcohols. Fully functional green fluorescent protein-tagged CER4 protein was localized to the endoplasmic reticulum in yeast cells by confocal microscopy. Analysis of gene expression by reverse transcription-PCR indicated that CER4 was expressed in leaves, stems, flowers, siliques, and roots. Expression of a β-glucuronidase reporter gene driven by the CER4 promoter in transgenic plants was detected in epidermal cells of leaves and stems, consistent with a dedicated role for CER4 in cuticular wax biosynthesis. CER4 was also expressed in all cell types in the elongation zone of young roots. These data indicate that CER4 is an alcohol-forming FAR that has specificity for very-long-chain fatty acids and is responsible for the synthesis of primary alcohols in the epidermal cells of aerial tissues and in roots.